A randomized clinical study to evaluate the effect of denture adhesive application technique on food particle accumulation under dentures. Issue 4 (17th June 2019) - Atassi, Mounir; Milleman, Kimberly R.; Burnett, Gary R.; Sanyal, Susmita; Milleman, Jeffery L.
Abstract: Food ingress under dentures is a common problem that may be reduced by denture adhesive use. The objective of this study was to explore the effect of the mode of application of a denture adhesive on reducing accumulation of food particles under dentures. This was a single‐centre, controlled, single‐blind, randomized, three‐treatment, three‐period, crossover study in participants with complete, removable well‐fitting, well‐made upper/lower dentures. Treatments were: 1) experimental denture adhesive application (test adhesive) applied with a precision applicator as continuous strips; 2) marketed denture adhesive (positive control) applied using a flat ribbon nozzle as dabs; 3) no adhesive. Food‐occlusion testing was performed by assessing peanut particle migration under dentures with denture retention/stability evaluated using the Kapur Index (Olshan modification). Differences were assessed using an ANOVA model. Adhesive oozing and perceptions of the adhesives were assessed by questionnaire. All 83 randomized participants completed the study. There were no significant differences between positive control or test adhesives versus no adhesive, or between test adhesive and positive control, for mass of peanut particles recovered from dentures. Both adhesives had significantly higher retention and stability scores compared with no adhesive (all P < .01). Participants reported significantly higher scores for denture comfort, confidence, satisfaction and movement with both adhesives versus no adhesive (all P < .01). No differences in adhesive ooze were reported between adhesives. No adverse events were reported. In conclusion, there was no difference in performance, as measured by peanut particle mass recovered from upper/lower dentures, for the test adhesive, positive control and no adhesive.